Long term utility and sustainable effect of soil and water conservation measures - Ranade, D H; Jadav, M L; Swarup, Indu; Bhagat, D V (Indian Farming, 2021)
In this study, it was surprisingly observed that after the exit of All India Co-ordinated Research Project for Dryland Agriculture, there was an entry of a new generation of farmers in agriculture activities, village development process, and there was no adverse impact on soil and water conservation measures. Various measures that were constructed during 1991-2006, continue to support conserving soil and water, thus enhancing agricultural production and income of the farmers. Therefore, the hypothesis that measures in plimented are not being maintained by farmers after the termination of the project and it no longer helps the farmers, is found to be invalid. It is a fact that with the help of technical guidance, soil and water conservation measures constructed at suitable site are effective in a long term.